A familial disorder of altered DNA-methylation. Issue 6 (10th April 2014) - Caliebe, Almuth; Richter, Julia; Ammerpohl, Ole; Kanber, Deniz; Beygo, Jasmin; Bens, Susanne; Haake, Andrea; Jüttner, Eva; Korn, Bernhard; Mackay, Deborah J G; Martin-Subero, José I; Nagel, Inga; et al.
Abstract : Background: In a subset of imprinting disorders caused by epimutations, multiple imprinted loci are affected. Familial occurrence of multilocus imprinting disorders is rare. Purpose/objective: We have investigated the clinical and molecular features of a familial DNA-methylation disorder. Methods: Tissues of affected individuals and blood samples of family members were investigated by conventional and molecular karyotyping. Sanger sequencing and RT-PCR of imprinting-associated genes ( NLRP2, NLRP7, ZFP57, KHDC3L, DNMT1o ), exome sequencing and locus-specific, array-based and genome-wide technologies to determine DNA-methylation were performed. Results: In three offspring of a healthy couple, we observed prenatal onset of severe growth retardation and dysmorphism associated with altered DNA-methylation at paternally and maternally imprinted loci. Array-based analyses in various tissues of the offspring identified the DNA-methylation of 2.1% of the genes in the genome to be recurrently altered. Despite significant enrichment of imprinted genes (OR 9.49), altered DNA-methylation predominately (90.2%) affected genes not known to be imprinted. Sequencing of genes known to cause comparable conditions and exome sequencing in affected individuals and their ancestors did not unambiguously point to a causative gene. Conclusions: The family presented herein suggests the existence of a familial disorder of DNA-methylation affecting imprinted but also not imprinted gene loci potentially caused by a maternal effect mutation in a hitherto not identified gene.